2014
DOI: 10.7554/elife.02481
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-tail interactions of the coiled-coil domains regulate ClpB activity and cooperation with Hsp70 in protein disaggregation

Abstract: The hexameric AAA+ chaperone ClpB reactivates aggregated proteins in cooperation with the Hsp70 system. Essential for disaggregation, the ClpB middle domain (MD) is a coiled-coil propeller that binds Hsp70. Although the ClpB subunit structure is known, positioning of the MD in the hexamer and its mechanism of action are unclear. We obtained electron microscopy (EM) structures of the BAP variant of ClpB that binds the protease ClpP, clearly revealing MD density on the surface of the ClpB ring. Mutant analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
203
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(223 citation statements)
references
References 60 publications
(145 reference statements)
16
203
2
Order By: Relevance
“…8). Recently, Saibil and co-workers (45) showed that each AAAϩ ring of the EClpB hexamer simultaneously binds four ADP molecules. From this observation, the binding of four ATP molecules to one ring would be expected to activate the ATPase of another ring.…”
Section: Discussionmentioning
confidence: 99%
“…8). Recently, Saibil and co-workers (45) showed that each AAAϩ ring of the EClpB hexamer simultaneously binds four ADP molecules. From this observation, the binding of four ATP molecules to one ring would be expected to activate the ATPase of another ring.…”
Section: Discussionmentioning
confidence: 99%
“…Unfoldases bind to misfolded proteins and unfold them. [39] Disaggregases solubilize existing protein aggregates [370]. Some chaperones exhibit overlapping functions [371].…”
Section: Discussionmentioning
confidence: 99%
“…PDB IDs: Skp, 1SG2 [275]; trigger factor, 1W26 [19]; SecA, 2FSF [369]; Hsp90, 2CG9 [182]; GroEL/ES, 1AON [34]; ClpX, 3HWS [39]; ClpB, 4D2U [370]; DnaK, 4B9Q [371]; FhaC, 2QDZ [61]; BamA, 4K3B [64]; SecYEG, 3DIN [372]; TamA, 4C00 [67]; proteasome, 1YAR [75]; HslU/HslV, 1G3I [72]. See text and Table 1 for details.…”
Section: Figure Legendsmentioning
confidence: 99%
“…2A) using a cross-linking approach. We used gentle glutaraldehyde cross-linking conditions that were previously used to establish the oligomeric state of the related AAA+ ATPase ClpB (22), which was independently confirmed by structural means (23). Following cross-linking for a duration that was just sufficient to deplete free cofactor and Torsin (t = 10 min), two major species were observed in a 6-9% gradient gel ( Fig.…”
Section: Significancementioning
confidence: 99%